The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1161/circulationaha.122.061934
|View full text |Cite
|
Sign up to set email alerts
|

Placental Inflammation Leads to Abnormal Embryonic Heart Development

Abstract: BACKGROUND: Placental heart development and embryonic heart development occur in parallel, and these organs have been proposed to exert reciprocal regulation during gestation. Poor placentation has been associated with congenital heart disease, an important cause of infant mortality. However, the mechanisms by which altered placental development can lead to congenital heart disease remain unresolved. METHODS: In this study, we use an in vivo neutrophil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…These responses to infection reflect a host innate immune defence strategy to minimise impending tissue injury and spread of infection 70 . Despite serving as a protective strategy, this inflammation response disrupts the core functions of the trophoblast, particularly hormone and lipid metabolism, which could have profound impact on the transport of nutrients to the embryo and on fetal growth and organ development [71][72][73] . Inflammatory and stress conditions can induce a switch in metabolic demands 74 .…”
Section: Discussionmentioning
confidence: 99%
“…These responses to infection reflect a host innate immune defence strategy to minimise impending tissue injury and spread of infection 70 . Despite serving as a protective strategy, this inflammation response disrupts the core functions of the trophoblast, particularly hormone and lipid metabolism, which could have profound impact on the transport of nutrients to the embryo and on fetal growth and organ development [71][72][73] . Inflammatory and stress conditions can induce a switch in metabolic demands 74 .…”
Section: Discussionmentioning
confidence: 99%
“…The study by Ward et al 10 provides an experimental preeclampsia-like model in which NDPI leads to abnormal heart development and impaired adult cardiac function in the offspring. Further research is needed to demonstrate the relevance of the NDPI model for the study of preeclampsia, most crucially, whether it reproduces the key preeclampsia features of maternal hypertension and proteinuria.…”
Section: Can the Attenuation Of Placental Inflammation Be Therapeutic...mentioning
confidence: 99%
“…In this issue of Circulation , Ward et al 10 show that experimental neutrophil-driven placental inflammation (NDPI) in mice leads to abnormal placental development and loss of barrier function. This allows maternal placental inflammatory monocytes to migrate to the embryonic heart, skewing the composition of the resident cardiac macrophage population and altering ventricular structure.…”
mentioning
confidence: 99%
“…In one study, neutrophil‐triggered inflammation of the placenta was found to lead to inadequate placental development and a lack of barrier function. As a result, maternally derived inflammatory monocytes from the placenta may migrate into the embryonic heart and alter the structure of cardiac tissue and the normal composition of resident cardiac macrophages 6 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, maternally derived inflammatory monocytes from the placenta may migrate into the embryonic heart and alter the structure of cardiac tissue and the normal composition of resident cardiac macrophages. 6 The circulatory physiology of the fetus is different from that of the newborn. The right ventricle provides greater cardiac output from the second half of pregnancy until delivery.…”
Section: Introductionmentioning
confidence: 99%